2014
DOI: 10.1007/s11845-014-1176-2
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil requirements for preventing motor response to skin incision in healthy women anesthetized with combinations of propofol and dexmedetomidine titrated to similar Bispectral Index (BIS) values

Abstract: Propofol and its combination with dexmedetomidine have similar opioid requirements for preventing motor response to skin incision when titrated to similar BIS values. These findings indicate that adjunctive dexmedetomidine for general anesthesia has sedative but no opioid sparing effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
2
5
1
Order By: Relevance
“…Anesthetic sparing effect of dexmedetomidine was demonstrated in all the articles studying this effect. [678910111213141516171819202122] Our study echoes this finding with a significant reduction in propofol utilization. The difference in patient population (infratentorial intracranial procedures), anesthetic technique (neuromuscular blockade-free anesthesia), and the longer duration of surgery (397.8 ± 99.2 min) in our study did not alter this outcome.…”
Section: Discussionsupporting
confidence: 72%
“…Anesthetic sparing effect of dexmedetomidine was demonstrated in all the articles studying this effect. [678910111213141516171819202122] Our study echoes this finding with a significant reduction in propofol utilization. The difference in patient population (infratentorial intracranial procedures), anesthetic technique (neuromuscular blockade-free anesthesia), and the longer duration of surgery (397.8 ± 99.2 min) in our study did not alter this outcome.…”
Section: Discussionsupporting
confidence: 72%
“… 19 20 Our pilot study also showed that a loading dose of intravenous dexmedetomidine 1 µg/kg, followed by an infusion rate of 0.33 µg/kg/h, does not reduce intraoperative opioid requirements, irrespective of its sedative and sympatholytic properties. 21 Dexmedetomidine is a potent sympatholytic agent, which can inhibit sympathetic activation following surgical stimuli. In the previous and present studies, hemodynamic criteria were used as stress response indicators to guide intraoperative opioid administration upon adjunctive DEX administration in general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, during BIS-guided closed-loop anesthesia, intraoperative dexmedetomidine could decrease the remifentanil induction dose by 25 %, but not the maintenance remifentanil dose. In addition, Wu et al [20] reported that a bolus administration of dexmedetomidine 0.5 or 1.0 lg/kg could not reduce remifentanil requirement for preventing motorresponse to skin incision in healthy female patients. When dexmedetomidine is used as an adjuvant to general anesthesia, its remifentanil-sparing effect is still controversial Values are expressed as mean ± SD or numbers of patients.…”
Section: Discussionmentioning
confidence: 99%